The theology of violence - Bell, M; Bell, Mark (2002)
﻿This thesis investigates the theology of violence in early modern England. It finds that violence had an important place in the theology of the English Revolution, which is at variance with many twentieth-century perceptions of Christianity. After introducing these ideas in the first chapter, chapter two begins with an outline of the general conceptions of the relationship between the Divine and violence, contrasting the image of a God of peace with a God of war. It also outlines just war theory, which was central to early modern English views of legitimate violence. Additional aspects of contemporaries' conceptions involved ideas of authorisation, violence as punishment, and a hierarchy of legitimate violence. These ideas are further developed in chapter three, first with reference to the Elizabethan Homilies and then in relation to theologians during the civil wars. This discussion of theologies of obedience anticipates chapter four's analysis of the theologies of resistance in relation to the theology of violence. Chapter four addresses a variety of themes concerning the illegitimacy of suicide and the corresponding legitimacy of self defence. The chapter concludes by addressing the idea of direct divine authorisation for violence, which is modelled by the biblical Book of Joshua and developed by examining Calvin's commentaries on the text. Direct authorisation lays the groundwork for chapter five, which addresses the apocalyptic perspective in relation to the theology of violence. The three interrelated themes of anti-Catholicism, anti-idolatry, and a new dispensation are examined. In chapter six, the previous themes are considered in an analysis of the regicide. The discussion of the regicide not only draws on the preceding discussion of the theology of violence but also examines the "scapegoating" dimension of the execution of the king. The final chapter offers reflections on the importance of the theology of violence for the view of the English civil wars as "wars of religion."